2012
DOI: 10.1016/j.engstruct.2011.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate collapse strength assessment of damaged steel-plated structures

Abstract: In an unpredictable world where human intervention or unexpected environmental conditions can prevail, damage can occur to manmade structures. Whilst structural design allows for redundancy, or a structural capability beyond the general working load of the structure, it is necessary to be able to analyse and understand the residual capability of a damaged structure to ensure the safety of personnel in the vicinity of the structure and assess the potential to facilitate repair.Idealised Structural Unit Method (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
4
15
0
Order By: Relevance
“…This method is discussed in more detail by Underwood et al [19] and summarised later in Section 4 of this paper.…”
Section: Damaged Grillage Case 1 Results -Plate Damagementioning
confidence: 99%
See 4 more Smart Citations
“…This method is discussed in more detail by Underwood et al [19] and summarised later in Section 4 of this paper.…”
Section: Damaged Grillage Case 1 Results -Plate Damagementioning
confidence: 99%
“…Previous analysis by the authors [19] has shown that the damage aperture shape has minimal effect on the overall collapse strength of stiffened panels.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations